On Radµ-GP*property - Hadi, Reham; Khalid, Wasan (Iraqi Journal of Science, 2025)
Throughout this paper we depend on the concept of μ- small submodule to generalized the Jacobson radical called μ-Radical that lead us to present a generalization of (GP*) property.